Eponymous dermatological signs in bullous dermatoses - Sentamilselvi Ganapati (Wolters Kluwer Medknow Publications, 2014)
Clinical signs are evolved by clinicians through their careful clinical examination. Medical professionals are generally familiar with these signs because of the emphasis given to them by the teaching faculty while they were students. Some of these signs are eponymously named after the clinicians giving credit to their observation. Eponymous signs in vesiculobullous diseases such as Nikolsky sign and Asboe Hansen sign (Bulla spread sign) are well known and were described during the 19th and 20th century, respectively. Cerebriform tongue in pemphigus vegetans was described by Premalatha (1981) three decades ago and is well recognized and cited in several text books and articles in leading journals. All these signs are revisited below with an emphasis on cerebriform tongue in pemphigus vegetans which could eponymously be called as Premalatha sign.